Misfitting and Hater Blocking: A Feminist Disability Analysis of the Extraordinary Body on Reality Television - Cleary, Krystal (Disability Studies Quarterly, 2016)
This article analyzes three popular TLC programs that are emblematic of contemporary reality televisual representations of the extraordinary body: Abby & Brittany (2012), The Little Couple (2009-), and My Big Fat Fabulous Life (2015-). Extending Rosemarie Garland-Thomson's concept of "misfitting," I demonstrate how the non-normative body fits seamlessly into the mediated domain of reality television precisely because of its misfit in material and social spheres. The representational mode of these programs appears as a corrective to oppressive depictions of people with non-normative bodies, yet, I argue, the discourse of extraordinary normalcy built into the narrative framework of these programs is in fact supported by a scaffolding of normativizing logics that hinge upon casts members' whiteness, upward class mobility, and fulfillment of conventional gender and sexual norms. As such, I examine how specific bodies–heterosexual, white, gender normative, affluent–are called upon to perform disability on reality television. I assert that these programs dangerously depoliticize disability by narratively isolating it from other facets of identity and power, and furthermore regard ableism as an individual and moralistic matter perpetuated by antagonistic "haters" rather than a concern of the State.